2021
DOI: 10.1111/bjc.12338
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of tolerance for psychological pain in the relationship of childhood trauma to suicidal ideation in individuals with a substance use disorder

Abstract: Objectives The association between childhood trauma and suicidal ideation has been well documented in several populations, including individuals with a substance use disorder (SUD). However, a gap still exists in the literature regarding the mechanisms by which childhood trauma later impacts suicide risk. This cross‐sectional study tested the effect of childhood trauma on suicidal ideation, as well as the mediating effect of tolerance for psychological pain (managing the pain and enduring the pain) in that rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…In other words, adolescents exposed to more traumatic events in childhood were more likely to report a higher level of suicidal ideation. Indeed, adverse childhood experiences may cause lasting and invisible harm to individuals, be detrimental to children's attachment security, make them have traumatic thoughts and perform more self‐harm, and adversely affect their cognitive, emotional and behavioural adaptation (Martins et al, 2021; Stagaki et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, adolescents exposed to more traumatic events in childhood were more likely to report a higher level of suicidal ideation. Indeed, adverse childhood experiences may cause lasting and invisible harm to individuals, be detrimental to children's attachment security, make them have traumatic thoughts and perform more self‐harm, and adversely affect their cognitive, emotional and behavioural adaptation (Martins et al, 2021; Stagaki et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…character strengths, childhood trauma, perceived stress, suicidal ideation has been widely demonstrated in empirical studies (Cicchetti & Rogosch, 2002;Dunn et al, 2013;Gomez et al, 2017;Li et al, 2014;Martins et al, 2021;Toth & Cicchetti, 2013). In addition, prior evidence has shown that the relationship between childhood trauma and suicidal ideation can be explained by other important variables (Miller et al, 2013; and that intervention of these intermediate factors is beneficial to alleviating suicidal ideation (Bahk et al, 2017).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In 2,259 Chinese students, a mediating effect of psychological pain on the relationship between emotional abuse and suicidal ideation was found [ 46 ]. Likewise in a clinical setting, Martins et al [ 47 ] report a direct effect of CT on suicidal ideation in 102 subjects with substance abuse disorder. This effect, however, vanished when the capacity to manage psychological pain was introduced as mediator.…”
Section: Introductionmentioning
confidence: 99%
“…This relationship highlights the importance of considering childhood trauma in the assessment and treatment of physical health conditions, advocating for an integrated approach to care that addresses both psychological and physical health needs. The mediating role of various psychological factors, such as tolerance for psychological pain, in the relationship between childhood C E-ISSN: 3041-8542 trauma and adverse outcomes such as suicidal ideation, points to the complexity of trauma's effects on mental health (Martins et al, 2021). These findings emphasize the need for interventions that target specific psychological mechanisms, potentially mitigating the impact of childhood trauma on adult mental health.…”
Section: Introductionmentioning
confidence: 99%